The impact of authoritarian systems on the rise of transnational Islamist movements: Egypt, Saudi Arabia & the path to Al Qaeda - El-Bakry, Rehab (AUC Knowledge Fountain, 2010)
The events of September 11, 2001 have had a profound impact on the world we live in today. Not only have they changed the perception of rights and freedoms in both the developed and developing worlds, but these events brought violent political Islamist movements from the fringes of international politics to the forefront of world politics. Suddenly movements that were once seen as an issue for the Muslim world became a concern for countries worldwide as they struggled to understand the causes behind the rise of Islamist violence and figure out ways to address it. By and large, Islamist movements, violent and non-violent, find roots in the Arab world. The authoritarian nature of these systems, which prioritizes stability of the system and the ability of regimes to remain in power over inclusion of the public and various opposition groups, have often dealt with these movements through attempts of cooption into the system or isolation, which ranges from preventing them from participating in the legitimate system to full repression through incarceration and torture. It is largely due to isolation by these systems that many Islamist movements have not only turned to violence but adopted transnational modes of operation whereby a movement based in one country will carry out violent activities in a second to bring about change in a third. This study trances the dealings of the Egyptian and Saudi Arabian governments with their respective Islamist movements with particular emphasis on tactics of cooption and isolation adopted by these governments. It also argues that these tactics played a fundamental role in driving these movements to alter their mode of operation from limiting their activities within the confines of the political system of individual countries to adopting global jihad against the states that help maintain these authoritarian systems in place. The end result Al Qaeda is hoping to achieve is the recreation of the Islamic Ummah, through the declaration of global jihad. Based on the study, a series of actions are recommended for several players including political analysts, the media, and political players both on the international and regional levels. These actions include the need for expanding authoritarian political theory to allow for the analysis of these new movements and to predict their future activities. Efforts need to be made to distinguish between Islam as a religion and political movements derived from it. There is also a need for limiting the demonization of Islam by the media in order to reduce the feeling that the religion is under attack, which would reduce the attraction of radical ideologies to young Muslims.